Ultrastructural Alterations of Midgut Epithelium, But Not Greater Wing Fluctuating Asymmetry, in Paper Wasps (Polistes dominula) from Urban Environments. (21st March 2018) - Polidori, Carlo; Pastor, Agustín; Jorge, Alberto; Pertusa, José
Abstract: Polistes paper wasps can be used to monitor trace metal contaminants, but the effects of pollution on the health of these insects are still unknown. We evaluated, in a south-eastern area of Spain, whether workers of Polistes dominula collected at urban and rural sites differ in health of midgut tissue and in fluctuating asymmetry, an estimate of developmental noise. We found that wasps collected at the urban sites had abundant lead (Pb)-containing spherites, which were less visible in wasps from the rural sites. Evident ultrastructural alterations in the epithelium of the midgut of the wasps collected at the urban sites included broken and disorganized microvilli, a high amount and density of heterochromatin in the nucleus of epithelial cells, cytoplasmic vacuolization and mitochondrial disruptions. Altogether, these findings suggest a negative effect on the transmembrane transport and a less efficient transcription. On the contrary, a healthy epithelium was observed in wasps from the rural sites. These differences may be preliminarily linked with levels of lead pollution, given that wasps from urban sites had double the Pb concentrations of wasps from rural sites. Level of fluctuating asymmetry was unrelated to wasp origin, thus suggesting no link between developmental noise and Pb-driven pollution.